Editorial Llamkasun - Medina Castro, Dario Emiliano (2022)
The National Autonomous University of Tayacaja Daniel Hernández Morillo, presents Vol. 3, No 2 (2022) of the Journal of Scientific and Technological Research "Llamkasun", which is a publication published every six months by UNAT and managed through the Open Journal System. Its objective is to publish articles resulting from completed research that retain a character of originality, usefulness, scientific and technological relevance; that contribute new knowledge on theoretical or practical aspects in the specialty of "Agrarian, Exact, Engineering and Materials Sciences", according to the indicated norms.